Exploration of the causal relationship between inflammatory cytokines and prostate carcinoma: a comprehensive Mendelian randomization study - Cai, Xianfu; Wang, Decai; Ding, Chenguang; Li, Yang; Zheng, Jin; Xue, Wujun (Frontiers in Oncology, 2024)
BackgroundProstate cancer (PCa) is one of the most prevalent malignancies affecting males; however, the role of inflammatory activity in the pathogenesis of this disease is not yet fully elucidated. Although inflammation is recognized as being closely associated with the onset and progression of PCa, the specific causal relationships between individual inflammatory factors and the disease require further clarification.MethodsMendelian randomization (MR) methodologies can mitigate bias by utilizing whole-genome sequencing data, leveraging specific genetic variants to assess causal relationships between a given exposure and an outcome of interest. This research employed an MR approach to investigate the association between inflammatory cytokines and PCa.ResultsIn total, 44 inflammatory cytokines were evaluated in a large GWAS dataset to enable the drawing of robust conclusions. Elevated circulating C-reactive protein (CRP) and prostaglandin E2 (PGE-2) levels were related to greater PCa risk. The reverse Mendelian randomization (MR) study indicates a causal relationship between prostate cancer and stem cell factor (SCF) (P=0.025).ConclusionCRP and PGE-2 play crucial roles in the regulation of PCa development. Moreover, PCa may have an impact on SCF levels. Further research is imperative to elucidate whether these biomarkers can be effectively utilized to prevent or treat PCa.